Edutourism development model in unesco global geopark ciletuh palabuhanratu sukabumi district. Issue 1 (March 2021) - Arrasyid, R; Urfan, F; Darsiharjo,; Ruhimat, M; Setiawan, I; Logayah, D S
Abstract: This study aims to model the development of edutourism at the UNESCO Global Geopark (UGG) Ciletuh Palabuhanratu, Sukabumi Regency. The sample of the study area was Ciemas Subdistrict, Waluran Subdistrict, and Ciracap Subdistrict. Human samples of this study were divided into two groups, namely inhabitants and communities. The number of respondents involved was 126 people (inhabitants) and 3 people (representatives from three communities). There are three variables studied, that is: (1) inhabitants and community involvement in the development of the UGG Ciletuh Palabuhanratu; (2) inhabitants and community support for UGG Ciletuh Palabuhanratu edutourism activities; and (3) the role of inhabitants and community in the development of the UGG Ciletuh Palabuhanratu. Data collection techniques are interviews and questionnaires. Data obtained were analyzed quantitatively descriptive based on research variables. The results obtained are a model for the development of edutourism in the UGG Ciletuh Palabuhanratu which focuses on the role of the inhabitants and the community, increasing social capital, and patterns of regional development. The model will be used as a basis in the process of developing edutourism initiated by the community and supported by the community. The implementation of this model is expected to increase the independence of the community in managing the geopark area as a tourist destination.